2019
DOI: 10.1186/s12864-019-5848-1
|View full text |Cite
|
Sign up to set email alerts
|

The difference in serum proteomes in schizophrenia and bipolar disorder

Abstract: Background Purpose of study is revealing significant differences in serum proteomes in schizophrenia and bipolar disorder (BD). Results Quantitative mass-spectrometry based proteomic analysis was used to quantify proteins in the blood serum samples after the depletion of six major blood proteins. Comparison of proteome profiles of different groups revealed 27 proteins being specific for schizophrenia, and 18 – for BD. Protein set in schizophrenia was mostly associated w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
59
0
3

Year Published

2020
2020
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(65 citation statements)
references
References 95 publications
3
59
0
3
Order By: Relevance
“…Gray matter decreases in the anterior cingulate have been reported as markers of genetic liability to psychosis, while reductions in the superior temporal gyrus and cerebellum may be the first onset of the disease markers [22]. Quantitative proteomic analysis using mass spectrometry identified 27 proteins specific to schizophrenia [23].…”
Section: Discussionmentioning
confidence: 99%
“…Gray matter decreases in the anterior cingulate have been reported as markers of genetic liability to psychosis, while reductions in the superior temporal gyrus and cerebellum may be the first onset of the disease markers [22]. Quantitative proteomic analysis using mass spectrometry identified 27 proteins specific to schizophrenia [23].…”
Section: Discussionmentioning
confidence: 99%
“…A recent study from our group identified differentially expressed proteins in the serum of individuals with amphetamine use disorder compared with a healthy control group [ 23 ]. Moreover, prior clinical proteomic studies utilized serum samples to determine the levels of proteins in patients who had developed neurodegenerative diseases [ 24 , 25 ], neurodevelopmental disorders [ 26 , 27 , 28 ], major depressive disorder, and bipolar disorders [ 29 , 30 ]. In the present study, we investigate the expression changes of CUD patients’ serum proteins compared with healthy controls, using an untargeted proteomic approach employing two-dimensional (2D) alteration in gel electrophoresis (2D-DIGE) coupled with mass spectroscopy (MS).…”
Section: Introductionmentioning
confidence: 99%
“…It is noteworthy that the top pathways for diurnal rhythms in prefrontal cortex gene expression that were different in schizophrenia compared to healthy controls are oxidative phosphorylation and mitochondrial dysfunction [ 99 ]. The results of proteomic studies also confirm gene expression dysregulation in schizophrenia [ 100 102 ]. Prabakaran et al showed that almost half of the proteins with altered expression were associated with oxidative stress responses and mitochondrial function [ 103 ].…”
Section: Molecular Mechanisms Of Oxidative Stress In the Pathogenementioning
confidence: 63%